MINIMIZING IDLE CAPACITY AND EFFICIENCY COST BY MODIFYING FEEDING AND FINISHING PF-I TO PRODUCE NPK - Dea Indiastuti Ramadany; Mu’tasim Billah; Kevin Esmunaldo; Sani Sani (Universitas Lambung Mangkurat, 2022)
With the policy of revoking the SP-36 fertilizer subsidy in 2022, an alternative is needed to minimize idle capacity and cost efficiency caused by stopping operations at the Phosphate I Fertilizer Unit. Based on national fertilizer stock data for NPK 15-10-12 fertilizer, there is a gap between the actual stock nationally and the minimum stock. The low actual stock nationally can lead to a scarcity of NPK fertilizer which can affect national food security. So as an alternative solution to solving the problem, the Phosphate I Fertilizer Factory is utilized to be able to produce NPK fertilizer. This problem is solved by using the PDCA Cycle (Plan-Do-Check-Action) method. Based on the data and facts in the field, it is known that the existing equipment condition of the Phosphate I Fertilizer Unit has not been able to produce NPK fertilizer. The results of the project found the best solution to the problem of equipment conditions at the Phosphate Fertilizer Unit I by modifying the feeding system facility which was originally manual to weigher based by installing 3 hoppers, dozometers, BC mixing, and DAP crusher in the Curing 250 Warehouse, then installing coating facilities and coloring NPK fertilizer on the existing cooler in the Phosphate I Fertilizer Unit, making key operating parameters, and conducting an On Job Training scheme for the Phosphate I Fertilizer Unit personnel at the NPK II/III/IV Plant. So with this modification, the Phosphate Fertilizer Factory I is expected to be able to produce NPK fertilizer.